Signaling System Transformation Scheme for Adding Memorized Train Location Function to Stabling Track of Shanghai Rail Transit Existing Lines - ZHAO Hongbin (Chengshi guidao jiaotong yanjiu)
[Objective] When Shanghai Rail Transit existing lines using CBTC (communication-based train control) signaling system adopts the mainline night time storage mode, after powering up on the following day, the driver starts the train in restricted manual driving forward (RMF) mode based on wayside signal indication, and potential operational safety risks may arise during train positioning establishment process. [Method] The design principle of signaling system memorized location function, the current status of existing signaling system facilities and equipment, and design demands for memorized location function are analyzed; an improvement of stabling track wayside positioning equipment and on-board beacon reading device is proposed, and a renovation plan of adaptability upgrade is carried out for corresponding wayside on-board software. [Result & Conclusion] After implementing the signaling system renovation plan, the stabling tracks of Shanghai Rail Transit Line 6, Line 7, Line 8, Line 9, and Line 11 are equipped with memorized train location function. Currently, the applied mainline night time storage mode can achieve positioning directly for overnight trains in the following morning after trains powering up, and can quickly start operation in signal controlled mode.